2017
DOI: 10.1002/ajs4.19
|View full text |Cite
|
Sign up to set email alerts
|

Delivering decision making support to people with cognitive disability — What has been learned from pilot programs in Australia from 2010 to 2015

Abstract: The UNCRPD has generated debate about supported decision making as a way to better enable people with cognitive disability to participate in decision making. In Australia, between 2010-2015, a series of projects have piloted various models of delivering decision making support. A critical review was conducted on the program documents and evaluations of these pilot projects. The pilots were small scale, conducted by both statutory and non-statutory bodies, and adopted similar designs centred on supporting a dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…Families assumptions about their right to involvement in decision making had led in some instances to tensions with workers. Similar issues of who has the right to be involved in decision support have also arisen in research on decision support for people with acquired brain injury 2016a, 2016b, 2016c and the pilot support for decisionmaking programs in Australia (Bigby et al, 2017). This suggests that if more formal mechanisms for decisionmaking support are created, careful consultation will be important to help families understand any constraints to their support role.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Families assumptions about their right to involvement in decision making had led in some instances to tensions with workers. Similar issues of who has the right to be involved in decision support have also arisen in research on decision support for people with acquired brain injury 2016a, 2016b, 2016c and the pilot support for decisionmaking programs in Australia (Bigby et al, 2017). This suggests that if more formal mechanisms for decisionmaking support are created, careful consultation will be important to help families understand any constraints to their support role.…”
Section: Discussionmentioning
confidence: 80%
“…It was not clear from where family members derived support for their role in decision-making support. However, a review of the Australian pilot decision-making programs found that supporters whether family members or volunteers valued assistance from program coordinators to navigate the often complex issues they confronted in providing decision-making support (Bigby et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the friendless this necessarily entails establishing or finding equivalents for missing relationships (e.g., recruiting supporters or finding other sources of advice and support), while the correlative 'safeguards' obligation of Article 12(4) calls attention to ensuring an acceptable 'quality' of those relationships, including avoiding the risk of a relationship of dependence or domination (Arstein-Kerslake and Flynn 2017). All of this explains why SD trials have proved to be so resource intensive (Bigby et al 2017;Purcal et al 2017), even though their goals and achievements were often quite modest. 6 But of course it also highlights the matrix of socio-economic contributors to overlapping and cumulative barriers and disadvantages encountered by those to be assisted by SD, such as poverty or problematic behaviours compounding reliance on care, and heightening levels of 'control' or surveillance of their lives (for an introduction, (Goggin et al 2017)).…”
Section: Sd As a 'Relational' Socio-economic Right To Scarce Resources?mentioning
confidence: 99%
“…One thing that is crystal clear from the Australian pilot programs for SD is that, irrespective of whether they achieve the desired outcomes or not, programs of support piloted so far in Australia are very costly (Bigby et al 2017;Purcal et al 2017, pp 32-33, 49). So, in a real-world context, even though not everyone needs support (e.g., some in mental health) and costs will vary with the individual, some priority setting is inevitable: for no government has unlimited resources.…”
Section: Some Policy Challengesmentioning
confidence: 99%